Desiminasi Produk Teknologi Mesin Pengolah Pupuk Organik Desa Jati Malang Kecamatan Arjosari Kabupaten Pacitan - Heri Wijayanto; Didik Riyanto; Bambang Triyono (Universitas Serang Raya, 2018)
The problem faced by Jatimalang village farmers in increasing agricultural production is the problem of fertilizer. Fertilizerneeds is going to increase, while subsidized fertilizer by the government is limited and the price is expensive, so the farmers' income just a little. The use of organic fertilizer is an alternative to overcome the problem of fertilizer. The purpose of technological dissemination in Jatimalang , Arjosari , Pacitan is to solve the problem of farmers fertilizerneeds by processing the remaining agricultural materials (straw and other leaves) and animal waste into organic fertilizer. Processing of organic fertilizer by farmer group Lestari II still manual and cannot fulfill requirement of fertilizer. Dissemination technology of organic fertilizer processing machine consists of compost machine, sieving machine, and granulator. Utilization of appropriate technology is expected to improve the living standard of farmers in Jatimalang village. The processing of agricultural waste materials and animal waste into organic fertilizer by using fertilizer processing machine (granulator, enumerator and sifter, and stirrer) through the dissemination program of technology products to the community that carried out this resulted in an organic fertilizer that is beneficial to farmer group Lestari II, and some people in Jatimalang village. The product produce two kinds of fertilizer ie compost and solid organic fertilizer packed in sacks. Production of fertilizers using granulator equipment, enumerators and sieves, and stirrer can improve the productivity of fertilizer that has been done with a simple machine. The quantity of production increases, and the quality of the fertilizer yield is also increased as it is processed with a granulator that produces droplets of fertilizer which are easy to use.